Greenhouse gas emissions and Green Deal in the European Union - Mogoș, Radu Ioan; Petrescu, Irina; Chiotan, Radu Alexandru; Crețu, Romeo Cătălin; Troacă, Victor Adrian; Mogoș, Paula Liliana (Frontiers in Environmental Science, 2023)
Greenhouse emissions (GE) represent an element that influences the lives of all people on the planet. This action must be controlled and prevented because the negative effects are starting to show more and more in everyday life, sometimes with devastating consequences from a climate point of view and not only for the inhabitants of certain regions. At the European level, one of the main measures taken was the implementation of the Green Deal as a response to the fight against GE. In this article, a description is made of the main elements that influence GE, as well as the role of the Green Deal in this context. Two more cluster analyses are also carried out regarding GE at the European level. One analysis concerns the identification and evolution of the main groups of countries from this point of view, and the second analysis concerns the main fields in the industry. In the final part of the article the obtained results are analyzed, a discussion is added based on them and also a section of conclusion.